Pembelajaran Generasi Muda Sebagai Pelopor Keselamatan Dalam Mitigasi Gempa dan Audit Struktur Bangunan Pasca Gempa - Kristiana, Retna; Novika Candra Fertilia; Sediyanto; Agus Suroso; Ali Sunandar; Resi Aseanto (LP3M Universitas Putra Bangsa, 2024)
Indonesia faces a significant earthquake risk due to tectonic plate movement and volcanic activity. Most of these risks are borne by the housing sector which is highly vulnerable to damage from earthquakes. Although there have been standards and guidelines for earthquake-resistant homes, damage still often occurs due to a lack of public awareness and ability to implement proposed solutions. This caused a huge financial burden for the government in repairing and rebuilding houses. Education and knowledge about construction also play a role in the level of vulnerability of buildings to earthquakes. To address these issues, increasing youth awareness and understanding of earthquake mitigation and post-earthquake structure audits is essential. Through integrated training and educational programs, youth can become agents of change who play a role in spreading awareness of the importance of structural integrity checks for post-earthquake safety in their neighborhoods.